Complete plastid and 45S rDNA sequences allow authentication of Liriope platyphylla and Ophiopogon japonicus - Yeonjeong Lee; Hyun-Seung Park; Jae-Hyeon Jeon; Jee Young Park; Seung Hyun Kim; Jungmoo Huh; Sunmin Woo; Do-Won Jeong; Tae-Jin Yang (Current Plant Biology, 2022)
Liriope platyphylla F.T. Wang & Tang and Ophiopogon japonicus (Thunb.) Ker Gawl are morphologically similar perennial herbaceous plants belonging to the Asparagaceae family used as evergreen ornamental plants as well as for medicinal purposes. Complete plastid genomes (plastomes) and 45S nuclear ribosomal DNA (45S rDNA) sequences were obtained from two L. platyphylla accessions and one O. japonicus accessions using low-coverage, whole-genome data. Phylogenomic analysis using plastomes or 45S rDNA of the three accessions showed identical topology. Comparative analysis of the three accessions and representatives of 28 other Asparagaceae species revealed that L. platyphylla and O. japonicus are the most closely related species in the family Asparagaceae. The plastomes were 156,754–157,071 bp and the 45S rDNA transcriptional unit was 5906–5789 bp, providing super-barcoding information. Plastome sequences contained 817 single-nucleotide polymorphisms (SNPs) and 173 insertions or deletions (InDels) at the interspecific level and 88 SNPs and 56 InDels at the intraspecific level. 45S rDNA sequences contained 70 SNPs and 3 InDels at the interspecific level and 12 SNPs and 1 InDel at the intraspecific level. We developed four dominant and two codominant DNA markers based on the plastome diversity for authentication of L. platyphylla and O. japonicus and successfully applied these to ingredients distributed in the herbal medicine market.